A comparison of open, laparoscopic and robotic total mesorectal excision: trial sequential analysis and network meta‐analysis. (12th November 2019) - Zheng, B.; Zhang, X.; Wang, X.; Ge, L.; Wei, M.; Bi, L.; Deng, X.; Wang, Q.; Li, J.; Wang, Z.
Abstract: Aim: Total mesorectal excision (TME) for rectal cancer can be achieved by employing open (OpTME), laparoscopic (LaTME) and robotic (RoTME) approaches but which of these has the best outcome? The aim of present study is to identify the most effective technique for rectal cancer by comparing all outcomes. Methods: Randomized controlled trials (RCTs) which compared at least two TME strategies were identified by literature search of electronic databases of articles published to June 2018. Network meta‐analysis with trial sequential analysis was performed using a frequentist approach with random‐effects meta‐analysis. Data collection and analysis: We conducted a systematic search of PubMed, EmBase, the Cochrane Library, CNKI, and Web of Science. Titles and abstracts of the retrieved publications were independently and blindly assessed by two authors. Results: Twenty‐two RCTs with 4882 rectal cancer patients were included in this analysis. The trial sequential analysis demonstrated that the cumulative Z ‐curve crossed either the traditional boundary or the trial sequential monitoring boundaries, suggesting that OpTME resulted in a more complete TME specimen than LaTME (relative risk 1.05, 95% confidence interval 1.01–1.08). Network meta‐analysis showed there was no significant difference in the other comparisons. Based on the P score of completeness of the TME specimen and circumferential resection margin positivity, the best technique was OpTME, followed by RoTME and then LaTME. However, this order was reversed when complications and mortality were considered. RoTME led to better lymph node harvest. Conclusions: Although OpTME may give better pathological specimens, minimally invasive techniques may have advantages when considering lymph node harvest, complications and mortality. More RCTs are needed to determine which technique actually gives the best chance of survival.